2022
DOI: 10.3390/ijms232315232
|View full text |Cite
|
Sign up to set email alerts
|

EPLIN, a Putative Tumour Suppressor in Colorectal Cancer, Implications in Drug Resistance

Abstract: Colorectal cancer is a serious threat to human health. Poor prognosis and frequently reported drug resistance urges research into novel biomarkers and mechanisms to aid in the understanding of the development and progression of colorectal cancer and to optimise therapeutic strategies. In the current study, we investigated the roles of a putative tumour suppressor, EPLIN, in colorectal cancer. Our clinical colorectal cancer cohort and online databases revealed a downregulation of EPLIN in colorectal cancer tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…It is considered a putative tumour suppressor. Lower expression in tumour cells has been reported when compared to normal tissues and recovery of expression has been observed to reduce cell proliferation and tumour growth [77][78][79]. In prostate cancer, eplin loss promotes remodelling of the actin cytoskeleton, downregulation of E-cadherin, CK-8 and -18, increased cell migration and chemoresistance, collectively showing regulation of EMT [80].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a putative tumour suppressor. Lower expression in tumour cells has been reported when compared to normal tissues and recovery of expression has been observed to reduce cell proliferation and tumour growth [77][78][79]. In prostate cancer, eplin loss promotes remodelling of the actin cytoskeleton, downregulation of E-cadherin, CK-8 and -18, increased cell migration and chemoresistance, collectively showing regulation of EMT [80].…”
Section: Discussionmentioning
confidence: 99%
“…No. WBLUF0500, Merck-Millipore, Hertfordshire, United Kingdom) and a UVITech Imager (UVITech Inc., Cambridge, United Kingdom) ( Zeng et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of EPLIN in colorectal cancer and its mechanism of action was the innovative subject of the study of Zeng et al [5]. The study found that EPLIN is downregulated in colorectal cancer tissues compared to normal tissues and that this reduced expression is associated with poor clinical outcomes.…”
mentioning
confidence: 99%